Borderland circuitry: immigration surveillance in the United States and beyond - Muñiz, Ana (University of California Press, 2022)
"Political discourse on immigration in the United States has largely focused on what is most visible, including border walls and detention centers, while the invisible information systems that undergird immigration enforcement have garnered less attention. Tracking the evolution of various surveillance-related systems since the 1980s, Borderland Circuitry investigates how the deployment of this information infrastructure has shaped immigration enforcement practices. Ana Muñiz illuminates three phenomena that are becoming increasingly intertwined: digital surveillance, immigration control, and gang enforcement. Using ethnography, interviews, and analysis of documents never before seen, Muñiz uncovers how information-sharing partnerships between local police, state and federal law enforcement, and foreign partners collide to create multiple digital borderlands. Diving deep into a select group of information systems, Borderland Circuitry reveals how those with legal and political power deploy the specter of violent cross-border criminals to justify intensive surveillance, detention, brutality, deportation, and the destruction of land for border militarization"--